2023
DOI: 10.31234/osf.io/nhs6c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First impressions count: Therapists’ impression on patients’ motivation and helping alliance predicts psychotherapy dropout

Kristin Jankowsky,
Johannes Zimmermann,
Ulrich Jaeger
et al.

Abstract: ObjectiveWith meta-analytically estimated rates of about 25%, dropout in psychotherapies is a major concern for individuals, clinicians, and the healthcare system at large. To be able to counteract dropout in psychotherapy, accurate insights about its predictors are needed. MethodWe compared logistic regression models with two machine learning algorithms (elastic net regressions and gradient boosting machines) in the prediction of therapy dropout in two large inpatient samples (N = 1,691 and N = 12,473) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…One limiting factor that our study shares with similar research is a specific, fixed set of available predictor variables. In any case, there are further variables (e.g., patients' motivation to participate in the therapy at baseline; Jankowsky et al, 2023) that might incrementally explain treatment response. The present results have to be seen against this background: For example, we found that demographics had a negligible role in our models.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One limiting factor that our study shares with similar research is a specific, fixed set of available predictor variables. In any case, there are further variables (e.g., patients' motivation to participate in the therapy at baseline; Jankowsky et al, 2023) that might incrementally explain treatment response. The present results have to be seen against this background: For example, we found that demographics had a negligible role in our models.…”
Section: Strengths and Limitationsmentioning
confidence: 99%